(untitled) (Politeja, 2022)
THE ‘NEW PORTUGUESE’? AFRODESCENDANTS AND THEIR ROLE IN THE SOCIETY The aim of this article is to show the role that representatives of the complex category of Afrodescendants play in contemporary Portuguese society. It is a vast topic, interpretable from different perspectives and covering many issues, such as: hybrid identities and models of integration, educational paths and experiences in the labor market, political agency and civic engagement, activity in the field of culture, art (i.a. their increasingly important role in the music market) or sport. In this work, I refer to selected examples of socio-cultural activity of Afrodescendants within non-governmental organizations, as well as to their activity on the political scene in recent years. The background for the analyses concerning the people of African origins are postcolonial relations and ideas of decolonizing space and memory. An important context is also the International Decade for People of African Descent established by UNESCO (2015-2024) and the impact of this initiative on the emergence of different projects related to Afrodescendants in Portugal.